Narasi Kebijakan dalam Komunikasi Pemerintah Pada Fase Awal Implementasi Program Makan Bergizi Gratis - Salsabila Laily Tabayuni; Suwandi Sumartias; Rd. Funny Mustikasari Elita (Badan Pengembangan dan Pembinaan Bahasa, 2026)
The study addresses three research questions: how MBG's policy narrative was designed and framed as a gradual policy; how language and terminology choices were used to manage public expectations; and how crisis communication was applied in responding to issues and incidents that emerged during the early implementation phase. This research employs a qualitative approach using a case study method. Data were collected through semi-structured in-depth interviews with 11 informants from the Presidential Communication Office (KKK) and the National Nutrition Agency (BGN), supplemented by observation and document analysis. Data analysis followed the interactive model of Miles et al. (2014) through data condensation, data display, and conclusion drawing, interpreted using framing theory, Situational Crisis Communication Theory (SCCT), and Image Restoration Theory. The findings reveal three key results. First, MBG's policy narrative was consistently framed as a long-term human capital investment through the